Robust nonlinear control via feedback linearization and Lyapunov theory for permanent magnet synchronous generator- based wind energy conversion system - R. Cheikh; A. Menacer; L. Chrifi Alaoui; S. Drid (Frontiers in Energy, 2018)
In this paper, the method for the nonlinear control design of a permanent magnet synchronous generator based-wind energy conversion system (WECS) is proposed in order to obtain robustness against disturbances and harvest a maximum power from a typical stochastic wind environment. The technique overcomes both the problem of nonlinearity and the uncertainty of the parameter compared to such classical control designs based on traditional control techniques. The method is based on the differential geometric feedback linearization technique (DGT) and the Lyapunov theory. The results obtained show the effectiveness and performance of the proposed approach.